The Human Nature Perspective of the Tasik Malaya Village Community (Islamic Educational Philosophy Studies) - Suriyanti Suriyanti; Eka Yanuarti (Indonesian Journal for Islamic Studies, 2023)
This study aims to explore and know human nature, especially the perspective of the Tasik Malaya village community. By using a qualitative descriptive writing method, by obtaining data from observation, direct interviews. Informants in this study were residents of the Tasik Malaya village community including priests and housewives. The research results obtained informationHumans are special creatures, because why? humans are given the potential by the creator in the form of thoughts to act, act and with the potential they already have which can later direct the individual himself to a positive path and be able to regulate and control himself in determining his future destiny. Conclusion: Human behavior in dealing with life, can be a benchmark for good or bad someone in the eyes of society. Attitude reflects our personality. How a person behaves and how he behaves is a form of identity that he has.